Intra-industry trade by types: what can we learn from Portuguese data? - Crespo, N.; Fontoura, M. P. (Review of World Economics, 2004)
We provide evidence on intra-industry trade (IIT) in the Portuguese case from 1994 onwards by disentangling vertical from horizontal IIT with two different indexes—the Grubel-Lloyd and the so-called CEPII index- and analyse the determinants of both IIT types. Distinct explanatory factors are identified for each IIT type and we confirm the comparative advantage explanation in the vertical case. The regression results are robust to different estimation methods and to alternative IIT indexes. Nonetheless, sensitivity of the IIT levels to the arbitrary criterion of the CEPII measurement points out to the Grubel-Lloyd index as a preferable method.